Insomnia, excessive daytime sleepiness, anxiety, depression and socioeconomic status among customer service employees in Canada - Faustin Armel Etindele-Sosso (Sleep Science, 2020)
Objective: It is the first study investigating deeply symptoms of neuropsychiatric diseases among a large population of customer service employees (n=1238, 640 females and 598 males). The study’s goals were document presence of sleep disorders, anxiety and depression among customer service advisors and determine the influence of the socioeconomic status (pSES), duration in position and full-time or part-time shift on the diseases above. Methods: Linear regressions and ANOVA with a Tukey multiple comparisons of means was performed to analyze correlation and differences between citizens, international students and immigrants in their pSES and neuropsychiatric diseases. Results: Customer service employees (578 Canadians, 264 immigrants and 358 international students) are in majority undergraduate students (286 men and 289 females) with a high school degree (280 men and 308 women). They work full-time (560 men and 548 women) and are single (420 men and 560 women). Among customer service advisors, the time spent as an advisor was an excellent predictor of insomnia, sleepiness and anxiety (respectively with R2=91,83%, R2=81,23% and R2=87,46%) but a moderate predictor of depression (R2=69,14%). The pSES was a moderate predictor of sleep disorders (respectively R2=62,04% for insomnia and R2=53,62% for sleepiness) and strongly associated with anxiety and depression (R2=82,95% for anxiety and R2=89,77% for depression). Discussion: Insomnia, sleepiness and anxiety are more prevalent for full-time employees (higher for immigrants and international students compared to Canadians) compared with part-time employees, while depression was similarly higher for Canadian and immigrants compared to international students. Regarding full-time employees, symptoms of insomnia, anxiety and depression were higher for men compared to women. Regarding part-time employees, symptoms of insomnia and sleepiness were higher for women compared to men. Employees working full-time with rotating shifts are more exposed to insomnia, sleepiness and anxiety than employees working part-time. More research is needed to understand mental health of customer service employees regardless of their area and it is worthy of interest to study the link between sleep disorders and mood disorders with work conditions. Here some practical suggestions are made to reduce neuropsychiatric disorders for customer service employees or to at least mitigate the work burden on their brains.